Optimization & characterization of chips developed from cabbage powder, maize and rice flour using simplex lattice mixture design - Prachi Deshmukh; Dhanashree Patil; Prasanna P Bhalerao; Ashish Dabade; Sachin K Sonawane (Food Chemistry Advances)
This study employed a simplex lattice mixture design to optimize cabbage chips by blending cabbage powder, maize flour, and rice flour. Fourteen formulations were created using Design-Expert® software, with sensory attributes including crispiness, taste, appearance, aroma, and overall acceptability assessed. The approach revealed that cabbage powder (12 %), maize flour (10 %), and rice flour (27.97 %) effectively produced chips with desirable characteristics. Proximate analysis of the final chips (per 100 g) indicated 409.69 kcal energy, 70.97 g carbohydrates, 7.22 g protein, 10.77 g fat, 5.52 g total sugar, 4.04 % moisture, and 7.00 g ash. Mineral analysis revealed 9.48 mg calcium, 84.26 mg potassium, and 38.46 mg magnesium. This research optimizes cabbage chips, emphasizing their balanced nutrition and potential as a healthier snack.